A parameter for the assessment of the segmentation of TEM tomography reconstructed volumes based on mutual information. (December 2017) - Okariz, Ana; Guraya, Teresa; Iturrondobeitia, Maider; Ibarretxe, Julen
Highlights: Radon projections have been calculated from the segmented volume of a TEM tomography reconstruction of a sample. Mutual information between TEM images of the sample and their corresponding Radon projections has been calculated. The correlation between MI and a discrepancy coefficient for the segmented volume and the ideal volume has been verified. MI has been assessed by comparing it to another validated methodology for the selection of the optimum segmentation. Abstract: A method is proposed and verified for selecting the optimum segmentation of a TEM reconstruction among the results of several segmentation algorithms. The selection criterion is the accuracy of the segmentation. To do this selection, a parameter for the comparison of the accuracies of the different segmentations has been defined. It consists of the mutual information value between the acquired TEM images of the sample and the Radon projections of the segmented volumes. In this work, it has been proved that this new mutual information parameter and the Jaccard coefficient between the segmented volume and the ideal one are correlated. In addition, the results of the new parameter are compared to the results obtained from another validated method to select the optimum segmentation.